The Roles of Shared Racial Fate and a Sense of Belonging With African Americans in Black Immigrants' Race-Related Stress and Depression. (March 2017) - Hunter, Carla D.; Case, Andrew D.; Joseph, Nancy; Mekawi, Yara; Bokhari, Ehsan
Objectives: The first goal was to examine whether race-related stress was associated with depression in Black immigrants, as has been found in African Americans. The second goal was to determine whether intergroup relations identity factors—Black immigrants' shared racial fate or sense of belonging with African Americans—were related to depression, above and beyond race-related stress. Third, we examined if Black immigrants' shared racial fate or a sense of belonging with African Americans moderated the relationship between race-related stress and depression.Method: Data were collected from 110 individuals who identified as first- or second-generation Black immigrants.Results: Greater race-related stress was related to higher depression. Greater endorsement of a sense of belonging with African Americans was related to lower depression over and above the influence of race-related stress; this was not the case for shared racial fate, which was not associated with depression. Neither shared racial fate nor a sense of belonging with African Americans moderated the association between race-related stress and depression. Intergroup relations facilitate our understanding of well-being in immigrant populations.